The Role of TikTok Social Media in Shaping Consumptive Behavior among Generation Z in Denpasar City - I Gede Indra Adi Prasetya; I Nyoman Indra Kumara (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of TikTok social media in shaping consumptive behavior among Generation Z in Denpasar City. Along with the rapid development of digital communication, TikTok has transformed from an entertainment platform into a persuasive medium that promotes consumption through lifestyle representation, influencer content, and integrated shopping features. This research employs a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews with Generation Z TikTok users and a local influencer, supported by observations and document analysis. The analysis is guided by the Uses and Gratifications Theory, the Circular Model of SOME (Share, Optimize, Manage, and Engage), and Consumer Behavior theory. The findings indicate that TikTok encourages consumptive behavior through continuous exposure to promotional content, algorithmic reinforcement, emotional appeal, and social validation. Generation Z actively uses TikTok to fulfill cognitive needs such as product information, affective needs such as entertainment and emotional satisfaction, and social needs related to belonging and identity. As a result, purchasing decisions are often driven by emotions, trends, and fear of missing out (FoMO), rather than rational evaluation of needs. This study concludes that TikTok plays a significant role not only in stimulating impulsive buying behavior but also in shaping long-term consumptive lifestyles among Generation Z in Denpasar City.